Branched and ionic β-Cyclodextrins multilayer assembling onto polyacrylonitrile membranes for removal and controlled release of triclosan. (20th January 2017) - Pérez-Álvarez, Leyre; Matas, Janire; Gómez-Galván, Flor; Ruiz-Rubio, Leire; León, Luis M.; Vilas-Vilela, Jose Luis
Highlights: bβCDs polyelectrolyte multilayers were assembled onto hydrolyzed PAN membranes. LbL assembling and degradation was monitored by XPS, FTIR and labelling with FA. Surface coating is degraded in 8 h but interior coating remains more than 25 days. TR removal from water was successfully accomplished by bβCDs/PAN membranes. Maximum TR release from multilayered membranes takes place in the first 24 h. Abstract: The present study summarizes the formation and characterization of multilayers of polyacrylonitrile (PAN) membranes with β-cyclodextrin derivatives in order to be potentially interesting for triclosan (TR) controlled delivery with antibacterial purposes, as well as, for the removal of TR from wastewater. With this object, cationic and anionic branched β-cyclodextrins (bβCDs) were incorporated by layer-by-layer (LbL) process onto previously synthesized and hydrolyzed PAN membranes. FTIR, XPS and labelling with fluoresceinamine (FA) let to study the formation and stability of the prepared multilayered systems. TR is a widely used antibacterial and antifungal agent with proven ability to inhibit bacterial growth that, however, recently has shown a potential toxicity. The ability of obtained bβCDs/PAN multilayered membranes to retain TR in water was evaluated by two different loading procedures. The delivery kinetic profile of TR from loaded membranes was also analyzed showing the maximum release in the first 24 h.